Influence of the specimen preparation and geometry on the measured static tensile properties of a woven fabric‐reinforced thermoplastic: Einfluss der Probenpräparation und ‐geometrie auf die gemessenen statischen Zugeigenschaften verstärkter Thermoplaste mit Gewebestruktur. Issue 11 (11th November 2016) - Bauer, C.; Hausmann, J.; Schalk, T.
Abstract : Endless‐fiber reinforced thermoplastics combine high material stiffness and strength with a good processability. In this work the influences of different specimen geometries and preparation methods on the measured tensile properties of such materials are investigated. Due to the material performance high test forces must be applied which often exceeds the possibilities of some standard test facilities. Therefore the influence of the specimen width on the tensile properties is investigated with the objective to allow a deviation from the test standard to reduce the necessary test forces by smaller specimen cross‐section. Polyamide 6, often used as matrix material for thermoplastic composites, shows a bad bonding behavior regarding the application of end tabs which are necessary for gripping in the testing machine. Therefore, different adhesive systems were tested. Alternatively, a tapered specimen geometry for cyclic tensile‐compression tests is examined with respect to the buckling and fracture behavior.